HYDROPONIC AND TOGA INNOVATIONS: SOLUTIONS FOR UTILIZING LIMITED LAND IN KETIMANG VILLAGE - Paduppai, Andi Mardiana; Dewi, Liza Amalia; Sanjaya, Aji; Sehato, Aulia Rohimi; Krismawati, Mardian (Journal of Social Comunity Services, 2025)
Objective: Limited agricultural land in rural areas due to land conversion drives the need for innovation in farming, and this study aims to implement a hydroponic system and a Family Medicinal Garden (TOGA) as an alternative cultivation method in the limited space of the Ketimang Village community, Wonoayu District, Sidoarjo Regency. Method: The methods used include clearing the planting area, sowing seeds, and arranging plants according to function and aesthetics. Result: The results of the study indicate that the community can utilize limited land to obtain fresh vegetables and family medicinal plants, while simultaneously increasing food security and household economic opportunities. Novelty: The application of the hydroponic system and TOGA has proven to be efficient, productive, and has the potential to provide added value through sustainable management.